2014
DOI: 10.1088/0004-637x/782/2/71
|View full text |Cite
|
Sign up to set email alerts
|

SIMULATING THE FORMATION OF A SIGMOIDAL FLUX ROPE IN AR10977 FROMSOHO/MDI MAGNETOGRAMS

Abstract: The modeling technique of Mackay et al. is applied to simulate the coronal magnetic field of NOAA active region AR10977 over a seven day period (2007 December 2-10). The simulation is driven with a sequence of line-of-sight component magnetograms from SOHO/MDI and evolves the coronal magnetic field though a continuous series of non-linear force-free states. Upon comparison with Hinode/XRT observations, results show that the simulation reproduces many features of the active region's evolution. In particular, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
111
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(115 citation statements)
references
References 48 publications
4
111
0
Order By: Relevance
“…Structures compatible with magnetic flux ropes have been observed on an active region scale (Canou & Amari 2010;Jing et al 2010;Guo et al 2010b;Green et al 2011;Savcheva et al 2012;Gibb et al 2014;Jiang et al 2014) and on a larger scale in coronal cavities (Gibson et al 2010;Rachmeler et al 2013;Gibson 2015;Bak-Steslicka et al 2016). The standard flare model requires a mechanism that triggers the onset of the flux rope eruption, resulting in the phenomenology observed during solar flares.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Structures compatible with magnetic flux ropes have been observed on an active region scale (Canou & Amari 2010;Jing et al 2010;Guo et al 2010b;Green et al 2011;Savcheva et al 2012;Gibb et al 2014;Jiang et al 2014) and on a larger scale in coronal cavities (Gibson et al 2010;Rachmeler et al 2013;Gibson 2015;Bak-Steslicka et al 2016). The standard flare model requires a mechanism that triggers the onset of the flux rope eruption, resulting in the phenomenology observed during solar flares.…”
Section: Introductionmentioning
confidence: 95%
“…Structures compatible with magnetic flux ropes have been observed on an active region scale (Canou & Amari 2010;Jing et al 2010;Guo et al 2010b;Green et al 2011;Savcheva et al 2012;Gibb et al 2014;Jiang et al 2014) and on a larger scale in coronal Article published by EDP Sciences A26, page 1 of 11 A&A 601, A26 (2017) …”
Section: Introductionmentioning
confidence: 98%
“…Kliem et al (2013) already showed that our unstable models evolve through these stages in the MHD sense, but here for the first time we show that an MF simulation is sufficient to look at the evolution of several flare features. And since data-constrained and even data-driven MF simulations (e.g., Gibb et al 2014) are much faster than dataconstrained and the non-existent data-driven MHD simulations, n = 70,000 n = 110,000 The iteration number of the models from which we have taken these field lines is marked on the corresponding plots. The magnetic flux distribution is shown with red (positive) and green (negative) contours.…”
Section: Flare Loops and Hftsmentioning
confidence: 99%
“…In the work of Cheung and DeRosa (2012), the evolution of AR 11158 was modeled by driving the simulation with a temporal sequence of magnetograms to capture the AR from emergence to eruption (Gibb et al, 2014, used a similar approached for modeling AR 10977). This was motivated by previous studies using the MF approach to model the evolution of the global corona (Yeates et al, 2007(Yeates et al, , 2008Yeates and Mackay, 2009a,b;Yeates et al, 2010).…”
Section: Active Region Eruptions Following Flux Emergencementioning
confidence: 99%